Environmental Security and Environmental Crime (International Journal of Contemporary Security Studies, 2023)
Consideration of the complex security issue in modern conditions requires the inclusion of various aspects, among which a very current environmental aspect is unavoidable. The security consideration based on it, results in a special form of environmental security, as an unavoidable part of the overall security. Thereby two analytical security levels stand out: national and international. The analysis of environmental security includes a very important issue of tort in the domain of environment and appropriate forms of crime, which require special attention. Environmental crime begins from the environmental law, and is related to the normative approach in defining, monitoring and opposing various forms and degrees of commiting a tort. A complex analysis of environmental security and environmental crime indicates a causal relationship and the necessary activity to reduce environmental crime in order to increase environmental security and overall security. The considered connection indicates the need to increase the analytical attention to the reduction of environmental crime through the increase of human and organizational capacities, in the domain of general, and especially environmental security.
Keywords: ecology; security; environmental security; crime; environmental crime